Association of ERCC5 Genetic Polymorphisms With Cirrhosis and Liver Cancer. (18th August 2020) - Yang, Gang; Yang, Yuxia; Ma, Xin; Huang, Lijun; Li, Wenbin; Song, Xuejuan; Zhang, Huiqin; Liu, Wenwen; Lu, Juanjuan
Introduction: To explore association of excision repair cross-complementing 5 ( ERCC5 ) genetic polymorphisms with cirrhosis and liver cancer. Methods: A total of 365 patients were enrolled, including control group (n = 133), cirrhosis group (n = 122), and liver cancer group (n = 110). The genotyping of ERCC5 rs2016073, rs751402, rs2094258, rs2296147, and rs2296148 was measured by using MassARRAY iPLEX technology. Results: There were no significant differences in gender and drinking among the 3 groups ( P > .05). There were significant differences among the 3 groups in both age-group ≤60 and >60 subgroup patients. Locus rs2016073 was significantly different among 3 groups, and genotype GG (n = 0) was not observed in liver cancer group. As for locus rs751402, there were significant differences among 3 groups, and genotype AA (n = 0) was not observed in liver cancer group. As for locus rs2094258, there were no significant differences among 3 groups. Locus rs2296147 showed no significant differences among 3 groups ( P > .05), but genotype CC was not observed in liver cancer group (n = 0). As for locus rs2296148, there were significant differences among 3 groups, and genotype TC (n = 0) was not observed in cirrhosis group. Regression analysis found locus rs751402 had significant difference between control group and cirrhosis group, patients with genotype AA and genotype GG were more likely to have cirrhosis than those with genotype GA. Conclusion: Our study suggested that genotype AA, genotype GG of ERCC5 locus rs751402, and genotype TC of locus rs2296148 may be important targets for cirrhosis, while ERCC5 polymorphisms (rs2016073 and ERCC5 polymorphisms, rs2016073 with genotype GG, and rs751402 with genotype AA) may be potential markers for liver cancer.